2021
DOI: 10.13031/trans.14224
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Conductivity Measurement for Three Frozen and Unfrozen Soils in the Red River of the North Basin

Abstract: HighlightsHydraulic conductivity was measured in frozen and unfrozen soil conditions by a minidisk infiltrometer.In the RRB, frozen sandy loam and silty clay soils had the highest and lowest hydraulic conductivity, respectively.Three simple equations were developed for the three soils to predict frozen soil hydraulic conductivity.Freeze-thaw cycles reduced soil hydraulic conductivity.Abstract. Hydraulic conductivity (k) is a key parameter in describing water movement through a soil profile. In the Red River of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Considering all the peat samples, the average K s values of peat decreased as the average K s values are much higher than the threshold values (0.8 × 10 −5 m s −1 for site 1 and 0.2 × 10 −5 m s −1 for site 2). It has been reported that the response of hydraulic conductivity to freeze-thaw cycles is related to the initial soil moisture content (Roy et al, 2021). The soil organic matter (76.5 ± 0.4%) and the soil moisture content (0.67 ± 0.01 cm 3 cm −3 ) before freezing of site 2 samples were significantly higher than for site 1 samples (p < 0.01), which may be the reasons for the different threshold values.…”
Section: Figurementioning
confidence: 99%
“…Considering all the peat samples, the average K s values of peat decreased as the average K s values are much higher than the threshold values (0.8 × 10 −5 m s −1 for site 1 and 0.2 × 10 −5 m s −1 for site 2). It has been reported that the response of hydraulic conductivity to freeze-thaw cycles is related to the initial soil moisture content (Roy et al, 2021). The soil organic matter (76.5 ± 0.4%) and the soil moisture content (0.67 ± 0.01 cm 3 cm −3 ) before freezing of site 2 samples were significantly higher than for site 1 samples (p < 0.01), which may be the reasons for the different threshold values.…”
Section: Figurementioning
confidence: 99%
“…(1) the need for controlling frost heave (Hayashi, 2013;Nixon, 1991); (2) the need for establishing and improving the prediction model (Harlan, 1973;Li et al, 2018;Ming et al, 2016); (3) the need for predicting spring flood caused by snowmelt in seasonally frozen region (Roy et al, 2020(Roy et al, , 2021. Recently, with the application of an artificial freezing method for containment of hazardous solid/liquid waste contaminants (Wagner, 2013), the study on the hydraulic conductivity of frozen soil has flourished once again.…”
Section: Introductionmentioning
confidence: 99%